Geotechnologies for forest monitoring in the city of Nova Palma - Rio Grande Do Sul - BR - Facco, Douglas Stefanello; Benedetti, Ana Caroline Paim; Filho, Waterloo Pereira; Kaiser, Eduardo André; Osto, Janderlei Velasque Dal (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Human land occupation has always been associated to gathering natural resources, where it is necessary to know about land coverage and usage dynamics. This way, the purpose of this work is to investigate temporal dynamics of forest coverage, by geotechnologies such as Remote Sensing. Methodology starts by multitemporal mapping of forest coverage in the municipality of Nova Palma, located in the Quarta Colônia de Imigração Italiana (fourth colony of italian imigration), Rio Grande do Sul. Using software SPRING, in monitored classification of satellite images of Landsat 5 Satellite in the year of 1985 Landsat 8 Satellite in the year of 2014. Afterwards spatial analysis, by Spatial Lenguage for Algebric Geopressessing (LEGAL), it was able to determine the following situation: forestal regeneration, deforestation and maintenance. Results show that reforestation areas concentrate in the influence area of Usina Hidreletrica de Dona Francisca (Hydroeletric Plant of Dona Francisca). Areas of deforestation ocurred in areas that the land are being prepared to production. The maintenance was by areas of greater terrain declivity, hill tops and watershed surroundings, areas considered Areas of Permanent Preservation (Área de Presevação Permanente - APP). In conclusion, the forestal expansion process was predominant in the municipality during monitoration season.